Antecedentes da aprendizagem organizacional em cursos superiores de tecnologia : a experiência brasileira - Rübenich, Nilson Varella (My University, 2016)
The theme of this research refers to organizational learning in higher vocational education programs in Brazil, denominated as Cursos Superiores de Tecnologia. They constitute the main type of professional higher education in Brazil and were redesigned in the early 2000, with the prerogative to meet most current demands of the productive sector and to expand access to vocational higher education. In this context, those vocational oriented programs must be frequently revised, redesigned and reorganized, ensuring the adequacy to the needs of the changing market, assuming constant organizational learning. In this context, the general objective of this thesis is to examine the practices that contribute to organizational learning in Brazilian higher vocational programs, identifying organizational learning results from single and double loop cycles and evaluating the results through the indicators of the Brazilian education ministry (MEC). The specific objectives are: a) to identify the practices that contribute to organizational learning processes in higher education vocational programs; b) to identify the outputs of the productive organizational learning of single and double loop cycles in higher education vocational programs; c) to correlate the practices that contribute to the learning processes in the programs with the outputs of productive organizational learning of single and double loop cycles with the current performance in indicators of MEC. To meet those objectives, a theoretical research was developed on the themes of organizational learning and on vocational higher education in Brazil, which culminated in a theoretical model including three macro hypotheses. The research was conducted in two distinct phases. The first phase had a qualitative approach, based on interviews with programs coordinators, and sought to identify practices that contribute to the organizational learning processes and their outputs, outlining sub-hypotheses and serving as a basis for the construction of a quantitative data collection instrument. The second phase of research was a survey, where professors from those programs acted as respondents. A total of 292 responses were received, which were the basis of a multivariate data analysis. An exploratory factor analysis was performed, which aimed to purify the model and validate the data collection instrument. A structural equation modeling was conducted to test the formulated hypotheses. The results show that the seven identified antecedents that contribute to organizational learning had an impact on the results, either with outputs of organizational learning or in results of the programs in the MEC evaluation system. The strongest relationships are between: a) the practices about MEC indicators and the learning of single and double loop cycles; b) the informal meetings between the teachers and the evaluations results of the program; c) the partnerships with companies and organizations and the learning of single loop cycle; and d) the contact with non-academic professionals and the student's performance in national exams (ENADE). As a theoretical contribution, this thesis presents a framework for the study of organizational learning in Brazilian educational environment, particularly in higher vocational education.
O presente trabalho tem como tema a aprendizagem organizacional em cursos superiores de tecnologia. Estes cursos são o centro da educação profissional em nível superior no Brasil. Eles foram reformatados, no início da década de 2000, com a prerrogativa de atender demandas mais atuais do setor produtivo e a de ampliação do acesso à educação superior. Desta forma, entendese que os cursos de formação de tecnólogos devem ser frequentemente revistos, redesenhados e reorganizados, garantindo a adequação às necessidades do mercado em constante transformação, pressupondo constante aprendizagem organizacional. Neste contexto, o objetivo geral desta tese foi de analisar práticas que são atecedentes para a aprendizagem organizacional em cursos superiores de tecnologia (tecnólogos), identificando resultados de aprendizagens organizacionais de ciclos simples e duplo e avaliando os resultados destas aprendizagens nos indicadores do MEC (SINAES). Como objetivos específicos, buscou-se: a) identificar práticas que contribuam para processos de aprendizagem organizacional em cursos superiores de tecnologia; b) identificar outputs de aprendizagens organizacionais produtivas de ciclos simples e duplo em cursos superiores de tecnologia; c) relacionar as práticas que contribuem com os processos de aprendizagem nos cursos com os outputs de aprendizagens organizacionais produtivas de ciclos simples e duplo e o desempenho do curso nos indicadores do SINAES. Para atender estes objetivos, foi desenvolvida base teórica sobre aprendizagem organizacional e sobre a educação profissional em nível superior no Brasil, que culminou em um modelo teórico com com três macro hipóteses. A pesquisa foi realizada em duas fases distintas. A primeira fase teve abordagem qualitativa, baseada em entrevistas com coordenadores de cursos, e buscou indentificar as práticas que contribuiem para processos de aprendizagem organizacional e seus outputs, delineando variáveis e servindo de base para a construção de instrumento de coleta de dados quantitativos. A segunda etapa de pesquisa foi uma survey, tendo como respondentes professores de cursos superiores de tecnologia. Foram recebidas 292 respostas, que formaram a base de dados para análises estatísticas multivariadas. Foi realizada análise fatorial exploratória, que objetivou purificar o modelo e validar o instrumento de coleta de dados, e utilizou-se modelagem de equações estruturais para teste das hipóteses formuladas. Os resultados mostram sete antecedentes para aprendizagem organizacional. Estes impactam em resultados, seja com outputs de aprendizagem organizacional, seja em resultados dos cursos no sistema de avaliação do MEC. As relações mais fortes estão entre: a) as práticas decorrentes do SINAES e as aprendizagens de ciclos simples e duplo; b) as reuniões informais entre os professores e os resultados nas avaliações do curso; c) as parcerias com empresas e organizações e as aprendizagens de ciclo simples; e d) o contato com profissionais não acadêmicos e o desempenho dos estudantes no ENADE. Como contribuição teórica, a presente tese apresenta um framework para estudo da aprendizagem organizacional no ambiente educacional brasileiro, em especial na educação profissional em nível superior.
Keywords: Aprendizagem organizacional; Ensino superior - Brasil; Tecnólogos; Ensino profissional - Brasil; Universidades e faculdades - Administração; Organizational learning; Education, Higher - Brazil; Technologists; Professional education - Brasil; Universities and colleges - Management